Adrenal Lymphangioma Mimicking Renal Cyst: A Case Report and Review of the Literature - Murat Akand; Mustafa Kucur; Pınar Karabagli; Ozcan Kilic; Bedreddin Seckin; Serdar Goktas (Case Reports in Urology)
We present a case of a 44-year-old female who was evaluated for left recurrent flank and abdominal pain. Abdominal ultrasonography demonstrated a large cystic mass on the upper pole of the left kidney. Magnetic resonance imaging showed a large, homogenous cystic mass measuring  cm with well-defined contours, being hypointense on T1-weighted images and hyperintense on T2-weighted images on the upper pole of the left kidney without a distinct plan between adrenal gland. According to clinical and radiological findings, surgical excision was carried out with a subcostal flank incision. Histologic and immunohistochemical examination demonstrates that the definite diagnosis is cystic lymphangioma of the left adrenal gland. Adrenal lymphangioma is a very rare lesion. This is the unique case of an adrenal lymphangioma considered as a renal cyst because of its radiological appearance.